2020
DOI: 10.1016/j.bbr.2019.112386
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to gains during risky decision-making differentiates chronic cocaine users from stimulant-naïve controls

Abstract: Background Chronic cocaine use has been consistently associated with decision-making impairments that contribute to the development and maintenance of drug-taking. However, the underlying cognitive processes of risk-seeking behaviours observed in chronic cocaine users (CU) have so far remained unclear. Here we therefore tested whether CU differ from stimulant-naïve controls in their sensitivity to gain, loss, and probability of loss information when making decisions under risk. Method A sample of 96 participan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 59 publications
0
19
0
2
Order By: Relevance
“…In the real world, cocaine users engage in more risky sexual behavior and criminal activity than nonusers (Grella et al, 1995; Lejuez et al, 2005). In the laboratory, numerous behavioral instruments such as the Iowa Gambling Task (IGT) have been used to assess the impact of cocaine on risky decision making, and have consistently found that, similar to real-world findings, chronic cocaine use is associated with greater risk-taking behavior (Bornovalova et al, 2005; Fishbein et al, 2005; Gowin et al, 2018; Kluwe-Schiavon et al, 2020; Leland & Paulus, 2005; van der Plas et al, 2009; Verdejo-Garcia et al, 2007). High levels of risk taking associated with cocaine use can extend far into abstinence (Bolla et al, 2003; Verdejo-Garcia et al, 2014), which may render these individuals vulnerable to relapse.…”
mentioning
confidence: 88%
“…In the real world, cocaine users engage in more risky sexual behavior and criminal activity than nonusers (Grella et al, 1995; Lejuez et al, 2005). In the laboratory, numerous behavioral instruments such as the Iowa Gambling Task (IGT) have been used to assess the impact of cocaine on risky decision making, and have consistently found that, similar to real-world findings, chronic cocaine use is associated with greater risk-taking behavior (Bornovalova et al, 2005; Fishbein et al, 2005; Gowin et al, 2018; Kluwe-Schiavon et al, 2020; Leland & Paulus, 2005; van der Plas et al, 2009; Verdejo-Garcia et al, 2007). High levels of risk taking associated with cocaine use can extend far into abstinence (Bolla et al, 2003; Verdejo-Garcia et al, 2014), which may render these individuals vulnerable to relapse.…”
mentioning
confidence: 88%
“…The data were collected in the context of the Social Stress Cocaine Study (SSCP) at the Psychiatric Hospital of the University of Zurich. 15,25 The general exclusion criteria were a family history of genetically transmitted psychiatric disorders (h 2 >0.5, e.g., autism, schizophrenia, or bipolar disorder); any severe neurological disorder or brain injury; a current diagnosis of infectious disease or severe somatic disorder; a history of autoimmune, endocrine, or rheumatoid arthritis; intake of medication with potential action on the central nervous system or the physiological stress system during the previous three days; participation in a large previous study conducted by our lab, the Zurich Cocaine Cognition Study; 7,10 and (for women) being pregnant or breastfeeding. The criteria for inclusion of CU in the study were cocaine as the primary substance of use; a lifetime cumulative consumption of at least 100 g of cocaine, estimated by self-report; and a current abstinence duration of <6 months.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the extent to which these structural impairments are directly related to cocaine-induced brain pathology (neurotoxicity) rather than preexisting traits (predisposition) remains unclear. 8,9 Moreover, cocaine adulteration with neurotoxic compounds (e.g., the anthelmintic levamisole), 10,11 concomitant use of other illicit substances or alcohol, 12 and comorbidity with psychiatric disorders (e.g., depression) 12-15 might influence brain integrity in chronic cocaine users (CU) independently of cocaine intake itself. Considering the limitations of current diagnostic methods, which are mostly limited to cost-intensive neuroimaging measures, the introduction of new markers of active brain pathology may help clarify crucial questions on substance-induced brain pathology and provide new monitoring tools for physicians working in addiction medicine.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the Social Stress Cocaine Project (SSCP) 40 69 CU and 54 HC were recruited. In- and exclusion criteria were tested during a screening-session.…”
Section: Methodsmentioning
confidence: 99%